Confrontando un modelo DSGE con los datos (2019)
In this document we try to answer a key question in macroeconomic modeling. How much does a stochastic model of general equilibrium reproduce the data? To answer this question we use three metrics. First, we compare the statistical moments of the model with the data. Second, we perform a simulation of the cycles. Third, we compare the impulse-response of the DSGE model with those of an SVAR model. Additionally, the model is estimated using Bayesian methods. Taking into account data from the United States, on a quarterly frequency (1950-2019), the model replicates the behavior of the data relatively well, although certain differences in magnitudes are observed.